2017
DOI: 10.1103/physreva.95.022702
|View full text |Cite
|
Sign up to set email alerts
|

Elastic electron scattering from ortho-, meta-, and paraxylenes, C8H10

Abstract: Ab intio calculations and normalized experimental measurements of the differential and integral cross sections for vibrationally elastic scattering of low-energy electrons from orthoxylene, meta-xylene and para-xylene are presented. The calculated cross sections are obtained using the Schwinger multichannel method implemented with norm-conserving pseudopotentials. The differential cross sections are measured at incident energies from 1 eV to 30 eV and scattering angles from 10 o to 130 o. These cross sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Later work by our group for toluene by Sakaamini et al [18] showed good agreement with those of Kato et al [17] except at the lowest E 0 of 1.5 eV where we see a stronger dipole forward-scattering in significantly better agreement with the SMC theory [18]. Our group has also measured low energy elastic scattering for the ortho-, meta, and para-isomers of xylene (C 6 H 4 (CH 3 ) 2 ) [19] and find the DCSs of these isomers to be essentially very similar, but about a factor of two higher in magnitude than toluene, importantly showing the significance of the extra-CH 3 groups which were attached to the benzene ring to form toluene into xylene [19]. Our group has also measured elastic scattering from benzonitrile (C 6 H 5 CN), which has a nitrile (C ≡ N) radical attached to the benzene ring [20], at similar low E 0 values.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Later work by our group for toluene by Sakaamini et al [18] showed good agreement with those of Kato et al [17] except at the lowest E 0 of 1.5 eV where we see a stronger dipole forward-scattering in significantly better agreement with the SMC theory [18]. Our group has also measured low energy elastic scattering for the ortho-, meta, and para-isomers of xylene (C 6 H 4 (CH 3 ) 2 ) [19] and find the DCSs of these isomers to be essentially very similar, but about a factor of two higher in magnitude than toluene, importantly showing the significance of the extra-CH 3 groups which were attached to the benzene ring to form toluene into xylene [19]. Our group has also measured elastic scattering from benzonitrile (C 6 H 5 CN), which has a nitrile (C ≡ N) radical attached to the benzene ring [20], at similar low E 0 values.…”
Section: Introductionsupporting
confidence: 87%
“…Figure 5. Experimental DCSs for elastic scattering from several benzene related compounds (a) all at E 0 = 15 eV, (b) all at E 0 = 30 eV, except toluene at E 0 = 20 eV.Cho et al[16]; Sakaamini et al[18]; Khakoo et al[20]; (•) Sakaamini et al[19]; present work; Kato et al[17]; ( ) Cho et al[16].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In the present work, we present integral, differential and momentum transfer cross sections for elastic scattering from toluene as part of an effort to study benzene derivatives with substituting a -CH 3 group on one of the -H groups. We have also planned similar work on substituting two -CH 3 groups to produce o-xylene, m-xylene and p-xylene [13]. For all these targets we have conducted a joint experimental and theoretical study to provide low energy differential elastic and integral cross sections, and to compare our results with theory and other available (experimental) cross sections.…”
Section: Introductionmentioning
confidence: 99%